Preparation method of pH-responsive dual-release hydrogel for promoting diabetic wound healing

By designing PH response dual release of hydrogel, loading sodium diclphotenate and lipidin lipids, the rapid hemostasis, inhibiting inflammation and promoting blood vessels of diabetic wounds, solving the problem of excessive inflammation and continuous bleeding during the healing of diabetes wounds, solve the problem of diabetic wounds. , Achieve efficient wound healing.

CN118892573BActive Publication Date: 2025-01-28JILIN AGRI SCI & TECH COLLEGE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411390308.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-28
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

Diabetic wounds have problems with excessive inflammation, persistent bleeding and ooze accumulation during the healing process, and existing dressings cannot effectively promote healing and are prone to infection.

Method used

A pH response dual release of hydrogel is designed. By loading sodium dicotox (DS) and falling newbound lipids (AL) in hydrogels, the pH response characteristics of hydrogel are used to achieve the time and space control of drugs. DS quickly releases in a acidic environment to inhibit inflammation, and AL slowly releases the entire healing process to prevent infection and promote blood vessel production.

Benefits of technology

Achieve rapid hemostasis, inhibit inflammation, prevent infection, and promote the production of blood vessels, thereby accelerating the healing of diabetic wounds, and solving the problem of excessive inflammation, continuous bleeding and exudate accumulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118892573B_ABST
    Figure CN118892573B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of biomedicine and relates to a preparation method of a pH-responsive dual-release hydrogel for promoting diabetic wound healing. The method comprises the following steps: (1) preparing oxidized sodium alginate; (2) preparing astilbin liposomes; (3) preparing oxidized sodium alginate solution with distilled water, adding astilbin liposomes to obtain OSA@AL solution; dissolving carboxymethylated chitosan and diclofenac sodium in distilled water to prepare CMCS@DS solution; mixing the above two solutions in equal volumes, and preparing ALD hydrogel through Schiff base reaction. The hydrogel releases DS (diclofenac sodium) in the early stage of wound formation and slowly releases AL (astilbin liposomes) in the middle stage of wound formation. By loading DS and AL in different regions of the hydrogel and utilizing its pH-responsive characteristics, the spatiotemporal controlled release of the drug is achieved, so that the hydrogel can play a role in the four stages of wound healing (hemostasis, inflammatory response, proliferation and tissue remodeling), thereby accelerating diabetic wound healing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomedicine and relates to wound dressings, and in particular to a method for preparing a pH-responsive dual-release hydrogel for promoting diabetic wound healing. Background Art

[0002] The incidence of diabetes has increased significantly, affecting more than 400 million people worldwide. Diabetic nephropathy, heart disease, and skin ulcers are common complications of diabetes, among which diabetic skin ulcers are particularly difficult to treat and persistent. In the case of diabetes, the wound healing process is stalled in the inflammatory stage, which is characterized by an imbalance of proinflammatory cytokines and growth factors, excessive accumulation of reactive oxygen species (ROS), impaired cell proliferation, and inhibition of angiogenesis. In addition, chronic, difficult-to-heal wounds are susceptible to bacterial infection, which often leads to the formation of exudates and biofilms, further hindering the healing process. Therefore, scavenging reactive oxygen free radicals, inhibiting inflammatory responses, promoting angiogenesis, and controlling bacterial infections are key strategies for treating chronic diabetic wounds.

[0003] At present, the treatment of diabetic wounds mainly focuses on methods such as blood sugar control and debridement. However, due to the high cost of treatment, complex operation and easy infection, patients still face tremendous pressure both financially and mentally. Although wound dressings are an effective treatment method, traditional dressings can only isolate wounds and cannot effectively promote healing, and patients are painful when changing them. The ideal wound dressing should have good breathability, antibacterial, anti-inflammatory and antioxidant properties.

[0004] In order to effectively control wound healing and infection, it has become a top priority to develop multifunctional and high-performance wound dressings. Recently, wound dressings including electrospun nanofibers, sponges and hydrogels have been designed for wound healing. Among them, hydrogel is a three-dimensional hydrophilic polymer network with a structure similar to that of the extracellular matrix. Therefore, hydrogels have great application potential in tissue engineering, drug delivery and wound dressings. The introduction of reversible covalent chemical bonds is a promising method for designing injectable hydrogels. Common covalent bonds include Schiff base bonds, disulfide bonds, boron ester bonds and other reactions. Many dynamic covalent bonds can be decomposed under the stimulation of pH, ROS, temperature and enzymes to control drug release. In chronic wounds, persistent inflammation leads to increased ROS levels, the wound environment is acidic (pH 4.5-6.5), and infected bacteria produce lactic acid and acetic acid, which further lowers the pH. Therefore, designing hydrogels with pH response and drug release control is crucial for the treatment of chronic diabetic wounds.

[0005] Carboxymethyl chitosan (CMCS) is a biocompatible and biodegradable polymer material that contains amino cations, which can inhibit the synthesis of macromolecules on the bacterial surface and change the permeability of the cell wall, showing excellent hemostatic and antibacterial properties. CMCS can also be combined with bioactive substances to enhance its functionality, especially in the treatment of diabetic wounds.

[0006] Sodium alginate (SA) is a natural polysaccharide extracted from seaweed. It is non-toxic, highly biocompatible, has excellent gel-forming ability and good thermal stability, and is widely used in biopharmaceuticals, tissue engineering, and medical dressings. Its mechanical properties can be enhanced by chemical modification to generate oxidized sodium alginate (OSA). The hydroxyl groups of SA are converted into aldehyde groups during the oxidation process, and the aldehyde groups can be attached to the tissue surface by forming Schiff base bonds. Therefore, existing hydrogels often select oxidized sodium alginate (OSA) and carboxymethyl chitosan (CMCS) as matrices to form OS hydrogels. However, wound healing is a complex process, and existing hydrogel dressings can only work at certain stages, especially for chronic diabetic wounds. Hydrogel dressings need to have the functions of hemostasis, antibacterial and anti-inflammatory, antioxidant, and angiogenesis promotion; therefore, it is necessary to provide a pH-responsive hydrogel with hemostasis, antibacterial and anti-inflammatory, antioxidant, and angiogenesis promotion. Summary of the invention

[0007] In view of the above technical problems and defects, the present invention designs a novel dual-release hydrogel which can quickly stop bleeding and reduce inflammation of wounds by releasing DS (diclofenac sodium) in the early stage of wound formation, and prevent wound infection and promote angiogenesis by slowly releasing AL (astilbin liposomes) in the middle stage of wound formation. By loading DS and AL in different areas of the hydrogel and utilizing its pH response characteristics, the spatiotemporal controlled release of the drug is achieved. After the hydrogel is injected into the wound, it plays a rapid hemostatic effect in the healing process of diabetic wounds. The acidic environment causes the Schiff base bond to break, quickly releases DS, kills bacteria and inhibits inflammation, and continuously releases AL in a continuous acidic environment to promote angiogenesis, thereby achieving the effect of promoting diabetic wound healing.

[0008] To achieve the above object, the present invention adopts the following technical solution:

[0009] A method for preparing a pH-responsive dual-release hydrogel for promoting diabetic wound healing, comprising the following steps:

[0010] Step 1: Preparation of oxidized sodium alginate;

[0011] Using sodium periodate to oxidize sodium alginate to prepare oxidized sodium alginate;

[0012] Step 2: Preparation of astilbin liposomes;

[0013] First, a solution consisting of astilbin, soybean lecithin and cholesterol in a ratio of 10:1:1 was dissolved in a mixed solvent of 5 ml methanol and 20 ml chloroform; then, the organic solvent was removed by rotary evaporation in a 35°C water bath to form a dry lipid film, which was then treated in a freeze dryer to completely remove the residual solvent; then, 10 ml of 0.02 mol / L phosphate buffer was added to the lipid film and rotated to form a liposome suspension; finally, the liposome suspension was ultrasonically treated using an ultrasonic processor in an ice water bath, and then the unencapsulated astilbin was removed by centrifugation;

[0014] Step 3: Synthesis of ALD hydrogel;

[0015] Oxidized sodium alginate solution was prepared with distilled water, and astilbin liposomes were added to obtain OSA@AL solution; carboxymethylated chitosan and diclofenac sodium were dissolved in distilled water to prepare CMCS@DS solution; the above two solutions were mixed in equal volumes, and ALD hydrogel, i.e., pH-responsive dual-release hydrogel, was prepared through Schiff base reaction.

[0016] As a preferred embodiment of the present invention, the specific steps of step 1 are: taking 1.0 g of sodium alginate powder and dissolving it in 50 ml of distilled water, then adding 1.08 g of sodium periodate to the sodium alginate solution, and reacting it for 5 hours under light-proof conditions; then adding 1.5 ml of ethylene glycol, and continuing to react for 1 hour to neutralize the unreacted sodium periodate; using a dialysis bag with a molecular weight cutoff of 3500 Da for 3 days of dialysis, and obtaining white flocculent oxidized sodium alginate by freeze-drying.

[0017] As a preferred embodiment of the present invention, the pH of the phosphate buffer in step 2 is 7.2, and the liposome suspension is sonicated for 5 minutes using an ultrasonic processor with a power of 100 W in an ice water bath.

[0018] As a preferred embodiment of the present invention, the specific operation of removing the unencapsulated astilbin by centrifugation in step 2 is: centrifuging at 12,000 rpm for 30 minutes at 4°C to collect the drug-loaded lipid nanoparticles, i.e., astilbin liposomes.

[0019] As a preferred embodiment of the present invention, the concentration of the oxidized sodium alginate solution in step 3 is 10%, astilbin liposomes containing 100 μmol of astilbin are added, the concentration of carboxymethylated chitosan is 10%, and the amount of DS added is 20 μg / ml.

[0020] The present invention verifies the pH-responsive dual-release hydrogel prepared by the above method through a mouse tail amputation model and a liver hemostasis model. The results show that the hemostasis time and bleeding volume of the ALD group (OSA-CMCS loaded with astilbin liposomes and diclofenac sodium) are significantly shorter than those of the DS group (OSA-CMCS loaded with diclofenac sodium), the ASB group (OSA-CMCS loaded with astilbin), and the AL group (OSA-CMCS loaded with astilbin liposomes), and the hemostasis time and bleeding volume of the AL group are shorter than those of the ASB group. It is considered that the hemostatic performance is enhanced after the synergistic effect of astilbin liposomes (AL), diclofenac sodium (DS) and the hydrogel substrate. Therefore, the provided pH-responsive dual-release hydrogel can be used in the preparation of hemostatic materials for in vivo or in vitro wound hemostasis, which can effectively control the bleeding volume and greatly shorten the hemostasis time.

[0021] The present invention embeds diclofenac sodium (DS) and AL with anti-inflammatory activity into the hydrogel. It can be seen from the in vitro drug release results that the hydrogel is a pH-responsive dual-release hydrogel. In the early stage (inflammatory response stage), DS with anti-inflammatory effect can be quickly released in an acidic environment to inhibit the inflammatory response; at the same time, AL with antibacterial, antioxidant and angiogenesis-promoting effects can be continuously released during the entire process of skin wound repair. The spatiotemporal transmission of AL and DS enables the hydrogel to play a role in the four stages of wound healing (hemostasis, inflammatory response, proliferation and tissue remodeling), thereby accelerating the healing of diabetic wounds and solving the problems of excessive inflammation, continuous bleeding and accumulation of wound exudate in diabetic wounds; therefore, the hydrogel can be used in the preparation of materials that promote wound healing.

[0022] Advantages and beneficial effects of the present invention:

[0023] (1) The present invention prepares astilbin liposomes by a thin film dispersion method. The encapsulation efficiency of the astilbin liposomes (AL) is 91.69±1.84%, and the average particle size is 107.92±0.18 nm. The smaller particle size helps the liposomes to circulate longer in the blood and better perform targeted delivery, thereby exerting a therapeutic effect.

[0024] (2) The present invention embeds diclofenac sodium (DS) and AL with anti-inflammatory activity into the hydrogel. The in vitro drug release results show that the hydrogel is a pH-responsive dual-release hydrogel. In the early stage (inflammatory response stage), it can quickly release DS with anti-inflammatory effect in an acidic environment to inhibit the inflammatory response; at the same time, it can continuously release AL with antibacterial, antioxidant and angiogenic effects throughout the entire process of skin wound repair. The spatiotemporal transmission of AL and DS enables the hydrogel to play a role in the four stages of wound healing (hemostasis, inflammatory response, proliferation and tissue remodeling), thereby accelerating the healing of diabetic wounds.

[0025] (3) The hydrogel provided by the present invention has a loose porous network structure with interconnected pores, which helps to strengthen the gas exchange and nutrient transfer between the wound area and the external environment, thereby accelerating wound healing. In addition, it has good stability. After DS and AL are introduced into the hydrogel, more hydrogen bonds are formed between the polymer chains, making the internal network structure more perfect, enhancing the anti-deformation ability, and being more conducive to protecting the wound area.

[0026] (4) The hydrogel provided by the present invention exhibits good swelling properties and is completely degradable. The addition of AL not only fills the pores of the hydrogel, but also covers the polysaccharide polymer, reducing hydration, thereby slowing down the corrosion of the cross-linking bonds and delaying the collapse of the system, allowing the hydrogel to release drugs continuously for a long time and exert a therapeutic effect.

[0027] (5) The hydrogel provided by the present invention not only has good blood compatibility, but also has excellent antioxidant properties, which can reduce the damage of ROS in the wound site, protect cells from apoptosis, reduce the inflammatory response in diabetic wounds, promote angiogenesis and wound contraction, accelerate skin regeneration, and accelerate wound healing.

[0028] (6) The hydrogel provided by the present invention has an inhibitory effect of more than 90% on Escherichia coli and Staphylococcus aureus, which is mainly due to the rapid release of DS and the sustained release of AL, which makes it have a strong antibacterial and anti-inflammatory effect. This property can provide an antibacterial and anti-inflammatory environment for diabetic wound repair, which is beneficial to the actual protection of the wound site.

[0029] (7) The hydrogel provided by the present invention is non-toxic and has good biocompatibility. It can improve the migration and proliferation ability of keratinocytes (HaCaT cells) and maintain the normal function of keratinocytes; at the same time, it can also promote the proliferation ability of fibroblasts (L929 cells) and accelerate the healing of diabetic wounds.

[0030] (8) The present invention found through experiments on mouse tail amputation model and liver hemostasis model that the hemostasis time and bleeding volume of the ALD group were significantly shorter than those of the DS group, ASB group, and AL group, and the hemostasis time and bleeding volume of the AL group were shorter than those of the ASB group. This is considered to be due to the synergistic effect of astilbin liposomes (AL), diclofenac sodium (DS) and the hydrogel substrate to enhance the hemostatic performance. Therefore, the provided hydrogel can be used as a hemostatic material for in vivo or in vitro wound hemostasis, which can effectively control the amount of bleeding and greatly shorten the hemostasis time.

[0031] (9) The pH-responsive dual-release hydrogel provided by the present invention has rapid hemostatic properties, good biocompatibility and intrinsic antibacterial and antioxidant capabilities. The rapid release of DS exhibits significant antibacterial and anti-inflammatory effects, while the sustained release of AL can promote angiogenesis, thereby comprehensively accelerating diabetic wound healing and solving the problems of excessive inflammation, persistent bleeding and accumulation of wound exudate in diabetic wounds. It has great potential in the treatment of diabetic wounds. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 is the characterization of AL and hydrogel; where A is the particle size of AL; B is the Zeta potential of AL; C is the 50 nm TEM image of AL; D is the 100 nm TEM image of AL; E is the SA and OSA 1 HNMR hydrogen spectrum; F is the FTIR spectra of SA and OSA; G is the FTIR spectra of CMCS, OSA, OS, DS, ASB, AL and ALD; H is the SEM image (×200) of OS, DS, ASB, AL and ALD hydrogels;

[0033] Figure 2 is the performance of the hydrogel; where A is the frequency scan of the hydrogel; B is the time scan of the hydrogel; C is the swelling rate of the hydrogel; D is the degradation rate of the hydrogel; E is the DS release kinetics of the ALD hydrogel under different conditions; F is the AL release kinetics of the ALD hydrogel under different conditions; (* p <0.05,** p <0.01 indicates comparison with the control group);

[0034] Figure 3 is the performance of the hydrogel; wherein, A is the ABTS free radical scavenging rate of the hydrogel; B is the DPPH free radical scavenging rate of the hydrogel; C is the photo of the hydrogel hemolysis experiment; D is the quantitative graph of the hemolysis rate; E is the colony counting experiment of the hydrogel on Escherichia coli and Staphylococcus aureus; F is the quantitative analysis of Escherichia coli; G is the quantitative analysis of Staphylococcus aureus; (*p<0.05, **p<0.01 indicate comparison with the control group);

[0035] Figure 4 is the biocompatibility of the hydrogel; A is the HaCaT cell toxicity test of the hydrogel; B is the cell scratch healing rate of the hydrogel within 48 hours (n = 3); C is the image of the scratch experiment of HaCaT cells after incubation with the hydrogel for different time periods (n = 3);

[0036] Figure 5A is the live / dead staining of L929 cells after incubation with different hydrogel extracts for 1, 2, and 3 days; B is the cell viability of RAW 264.7 macrophages after treatment with different hydrogel extracts for 1 and 2 days (n = 6); C is the immunofluorescence image of RAW 264.7 macrophages stained with Nrf2 and NF-κB (green) after 2 days of treatment; (*p<0.05, **p<0.01, ***p<0.001 indicate comparison with the control group);

[0037] Figure 6 is the in vivo hemostasis of each group of hydrogels; A is a photo of the bleeding wounds in the mouse liver and tail hemostasis model; B is the amount of bleeding on the liver wound; C is the hemostasis time of the liver wound; D is the amount of bleeding on the tail; E is the hemostasis time of the tail wound; (the bar graph represents the mean ± standard deviation, n = 3, *p<0.05, **p<0.01);

[0038] Figure 7 The in vivo healing experiment and histopathological staining of hydrogel on type 2 diabetic wounds (T2D); A is a schematic diagram of establishing a diabetic wound model; B is the wound photos of different treatment groups on days 0, 3, 7, 14 and 21; C is the wound contraction rate of different treatment groups; D is the H&E and Masson staining images of different hydrogels; E is the quantification of collagen deposition; (*p<0.05, **p<0.01 indicate comparison with the control group);

[0039] Figure 8 is the effect of ALD hydrogel on TLR4 / NF-κB / MyD88 signaling pathway; A is Western blot analysis of TLR4 / NF-κB / MyD88 pathway; B is TLR4 / β-actin protein quantitative analysis; C is p-IκBα / IκBα protein quantitative analysis; D is MyD88 / β-actin protein quantitative analysis; E is p-NF-κB / NF-κB protein quantitative analysis; F is IL-1β / β-actin protein quantitative analysis; G is TNF-α / β-actin protein quantitative analysis; H is iNOS / β-actin protein quantitative analysis; (*p<0.05, **p<0.01 indicates comparison with the control group);

[0040] Fig. 9 is the effect of ALD hydrogel on the expression of HIF-α, PDGFA and VEGFA proteins; wherein, A is the western blot analysis of HIF-α, PDGFA and VEGFA; B is the quantitative analysis of HIF-α / β-actin proteins; C is the quantitative analysis of PDGFA / β-actin proteins; D is the quantitative analysis of VEGFA / β-actin proteins; (*p<0.05, **p<0.01 indicate comparison with the control group). DETAILED DESCRIPTION

[0041] In order to enable those skilled in the art to better understand the technical solution and advantages of the present invention, the present application is described in detail below in conjunction with the accompanying drawings, but it is not intended to limit the protection scope of the present invention.

[0042] 1. Materials and Methods

[0043] 1.1 Materials

[0044] Astilbin (ASB) was purchased from the National Institutes for Food and Drug Control (purity > 98.0%). Diclofenac sodium (DS) with a purity > 99.0%, carboxymethyl chitosan (CMCS, MW = 2240 kDa, deacetylation degree > 90%, substitution degree 90%), soybean phosphatidylcholine (SPC), and cholesterol (Chol) were purchased from Shanghai McLean Biochemical Co., Ltd. (Shanghai, China). Sodium alginate (SA, MW = 216.1 kDa) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Chloroform and methanol were provided by Shanghai Sinopharm Chemical Reagent Co., Ltd. (Shanghai, China). Sodium periodate was purchased from McLean Company, Shanghai, China. Lipopolysaccharide (LPS) was from Sigma-Aldrich Co., Ltd. (Shanghai, China). Escherichia coli and Staphylococcus aureus were from Shanghai Lu Wei; the hematoxylin-eosin (H&E) kit was purchased from Nanjing Jiancheng Bioengineering Institute. Live / dead cell staining kit, Masson staining kit, RIPA lysis buffer (P0013B) were purchased from Shanghai Biotech Co., Ltd.; 1,1-diphenyl-2-picrylhydrazyl radical (DPPH) and 2,2'-amino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) were purchased from Fuzhou Phygene Biotechnology Co., Ltd.; MTT was purchased from Aladdin Biochemical Technology Co., Ltd.; MyD88 was purchased from Beyotime Biotechnology (Wuhan, China); HRP-conjugated secondary antibodies, TLR4, IκBα, NF-κB, IL-1β, TNF-α, iNOS, HIF-1α, PDGFA, VEGFA, and β-actin were purchased from Proteintech, and p-IκBα and p-NF-κB were purchased from Arigo. All chemical reagents were of analytical grade.

[0045] 1.2 Animals

[0046] Sixty male ICR mice, aged 8 weeks and weighing 24-28 g, were purchased from Yisi Laboratory Animal Co., Ltd., Changchun, China (animal license: 2023-12-10-004). The mice were adapted to laboratory conditions (22 ± 2 °C, 60 ± 5% humidity, alternating light) for one week and randomly divided into different groups. All animal studies were conducted in accordance with the Guide for the Care and Use of Laboratory Animals of the National Research Council (GB / T35892-2018) and approved by the Laboratory Animal Management Committee of Jilin Agricultural University (NO. 2023-09-10-001).

[0047] 1.2.1 Cells

[0048] Human keratinocytes (HaCaT), mouse fibroblasts (L929), and RAW264.7 macrophages were purchased from Shanghai Fuheng Biotechnology Co., Ltd. DMEM high glucose medium and fetal bovine serum albumin (FBS) were purchased from Thermo Fisher (Beijing, China). Trypsin was purchased from Shanghai Biosharp. Phosphate buffered saline (PBS) was purchased from Solarbio Biotechnology Co., Ltd. (Beijing, China). Penicillin-streptomycin (100×) was purchased from Hyclone, USA. 96-, 12-, and 6-well plates were purchased from Corning, USA. DAPI staining solution was purchased from Shanghai Biyuntian Biotechnology Co., Ltd. The incubator temperature was controlled at 37°C, humidity was 95%, and CO2 concentration was 5%. The culture medium was changed once a day. The cell status was observed under a microscope every day. When the cells grew to more than 90%, they were digested and subcultured with 0.25% trypsin for subsequent experiments.

[0049] 1.3 Hydrogel preparation

[0050] 1.3.1 Preparation of OSA

[0051] 1.0 g of SA powder was dissolved in distilled water (DW, 50 ml), and then 1.08 g of sodium periodate was added to the SA solution and reacted for 5 hours under light-proof conditions. Subsequently, 1.5 ml of ethylene glycol was added and the reaction continued for 1 hour to neutralize the unreacted sodium periodate. Dialysis was performed for 3 days using a dialysis bag with a molecular weight cutoff of 3500 Da, and white flocculent OSA was obtained by freeze drying. The degree of substitution of OSA was determined to be 60% using the hydroxylamine hydrochloride method.

[0052] 5% (w / v) OSA aqueous solution and CMCS were dissolved in 4.0wt% phosphate buffer solution (PBS), and the mixed solution was poured into a 12-well plate and allowed to stand for 3 minutes to prepare OS hydrogel via Schiff base reaction.

[0053] 1.3.2 Preparation of Astilbin-Lips (AL)

[0054] First, a solution consisting of ASB, soybean lecithin, and cholesterol in a ratio of 10:1:1 was dissolved in a mixed solvent of 5 ml methanol and 20 ml chloroform. Then, the organic solvent was removed by rotary evaporation in a 35°C water bath to form a dry lipid film, which was then treated in a freeze dryer (vacuumed before freeze drying and the temperature was controlled at about -40°C) for 18 hours to completely remove the residual solvent. Subsequently, 10 ml of 0.02 mol / L phosphate buffer (PBS, pH=7.2) was added to the lipid film and rotated for 30 minutes to form a liposome suspension. Finally, the liposome suspension was sonicated for 5 minutes using an ultrasonic processor (produced by Shanghai Jingxin Experimental Equipment Technology Co., Ltd.) with a power of 100 W in an ice water bath. Because ASB has a low water solubility, high-speed centrifugation was used to remove unencapsulated ASB. The specific operation was: centrifugation at 12,000 rpm for 30 minutes at 4°C to collect the drug-loaded lipid nanoparticles (AL).

[0055] 1.3.2 Synthesis of ALD hydrogel

[0056] OSA (10%, w / v) solution was prepared in DW (distilled water), and AL (containing 100 μmol ASB) was added to obtain OSA@AL solution. CMCS (10%, w / v) and DS (20 μg / ml) were dissolved in DW to prepare CMCS@DS solution. The above two solutions were mixed in equal volumes and ALD hydrogel was prepared by Schiff base reaction.

[0057] In addition, the present invention abbreviates OSA-CMCS blank hydrogel as OS, diclofenac sodium loaded OSA-CMCS as DS, astilbin loaded OSA-CMCS as ASB, and astilbin loaded liposome hydrogel (ASB-Lips @OSA-CMCS) as AL for the convenience of subsequent experimental description.

[0058] 1.4 Characterization of ASB-Lips (AL)

[0059] 1.4.1 Analysis of AL encapsulation efficiency, particle size, zeta potential and polydispersity coefficient

[0060] Due to the poor water solubility of ASB, free ASB in the liposome solution can be removed by high-speed centrifugation. 0.5 ml of liposome solution was centrifuged at 12,000 rpm for 30 min at 4°C to obtain encapsulated ASB (W1) liposomes. 10 ml of methanol was added to the supernatant, and the emulsion was ultrasonically broken. 0.5 ml of liposome solution was added to 10 ml of methanol and ultrasonically broken for 5 min to obtain the total ASB in the liposome solution (Wtotal). Nanobrook 90 zeta (Brookhaven) was used to analyze the particle size, zeta potential and polydispersity index (PDI) of AL. The sample was diluted 10 times with distilled water, the test temperature was 25°C, the scattering angle was 90°, and all tests were measured in parallel 3 times. ASB detection was performed using HPLC (Waters, e2695, USA) at a wavelength of 290 nm. The mobile phase was acetonitrile (25%) and water (75%) at a flow rate of 1.0 ml / min. The stationary phase was a COSMOSIL C18-PAQ column (4.6 mm × 250 mm, 5 µm). The encapsulation efficiency (EE) was calculated.

[0061]

[0062] In the formula, is the amount of ASB encapsulated in the liposome, is the total amount of ASB in the liposome solution.

[0063] 1.4.2 Transmission electron microscopy

[0064] The morphology of AL was observed using a transmission electron microscope (TEM, JEM-1200 EX, Hitachi, Japan). AL was diluted with distilled water and dropped onto a carbon-coated copper grid to form a thin liquid film, which was then stained by adding 0.2% phosphotungstic acid. The film on the grid was dried at room temperature overnight, and then observed and photographed using a transmission electron microscope.

[0065] 1.5 Characterization of hydrogels

[0066] 1.5.1 OSA 1 HNMR

[0067] The structures of SA and OSA were identified using a 400 MHz NMR spectrometer (Bruker, 600 MHz AV NEO, Germany), and the degree of substitution (DS) of OSA was calculated. The OSA sample was dissolved in heavy water D2O at a concentration of 30 mg / mL, placed in an NMR tube, and detected using a spectrometer.

[0068] 1.5.2 Fourier transform infrared spectroscopy

[0069] The chemical structure of the hydrogel was characterized by Fourier transform infrared spectroscopy. The dried sample and KBr were ground into a uniform powder in a mortar and pressed into a sheet of appropriate thickness. The scanning wave number range was 4000-500 cm −1 , resolution 2cm −1 .

[0070] 1.5.3 Scanning Electron Microscopy (SEM)

[0071] The microstructure of the hydrogel surface was studied by SEM (Quanta250, Thermo Fisher, USA). Freeze-dried OS, DS, ASB, AL, and ALD hydrogels were cut into small pieces, attached to a sample plate, and gold-sprayed. Images were acquired using a 200x magnification lens for subsequent analysis.

[0072] 1.5.4 Rheological properties of hydrogels

[0073] The rheological properties of the hydrogels were tested using a Thermo Fisher Hackett rheometer. OS, DS, ASB, AL and ALD hydrogels were prepared into cylinders with a thickness of 2 mm. The test temperature was then set to 25°C, the test conditions were a frequency of 1 Hz, a strain of 1%, a gap distance of 1 mm, and a shear frequency of 0-500S. The storage modulus (G′) and loss modulus (G″) of the hydrogel wound dressings in different groups were observed as a function of strain and frequency.

[0074] 1.5.5 Swelling and degradation tests

[0075] The swelling of the hydrogels was determined by the weight change method. The swelling test was performed in PBS buffer (pH 7.4) at 37°C. The initial mass of the freeze-dried hydrogels (n = 3) was weighed and recorded as The swollen hydrogel was taken out at different time points, and the surface water was removed using filter paper, and its mass was recorded as The swelling ratio is calculated as: ;

[0076] For the in vitro degradation test, the degradation behavior of the hydrogel was also measured by measuring the weight change of the hydrogel. The initial mass of the hydrogel was recorded as The hydrogel was placed in PBS buffer (pH 7.4) at 37°C, taken out at a specific time point and the surface water was removed using filter paper, and its mass was recorded as The calculation formula of degradation rate (%) is:

[0077] ;

[0078] 1.6 In vitro drug release studies

[0079] DS and AL were placed in phosphate buffer (PBS) with different pH values ​​(pH=7.4 and pH=5.5) to simulate the drug release characteristics of hydrogels in alkaline and acidic environments. The samples were shaken at 100 r / min in a 37°C constant temperature water bath shaker, and 1 ml was sampled at specific time points (0.5, 1, 2, 4, 6, 8, 10, 12 and 24 hours) to measure the drug release amount, and then an equal volume of fresh PBS was added to maintain a constant volume of the release medium. High performance liquid chromatography (HPLC) was used for analysis, and the detection wavelength was set at 290 nm. The drug release rate curve was drawn to show the relationship between the release rate (%) and time.

[0080] 1.7 Antioxidant activity studies

[0081] Free radicals are ubiquitous biological metabolites in the body, and it is very important to inhibit free radical imbalance. In order to evaluate the antioxidant properties of ALD hydrogel, the present invention carried out ABTS free radical scavenging and DPPH free radical scavenging experiments. The free radical scavenging experiment was carried out according to the existing method.

[0082] 1.7.1 Determination of ABTS free radical scavenging rate

[0083] Mix the ABTS diammonium salt stock solution and K2S2O8 stock solution and place it in the dark for 12 hours. This solution is used as the ABTS working solution. 0.8 ml of the ABTS working solution was diluted and mixed with 0.2 ml of anhydrous ethanol as the blank control group. The absorbance value of the detection was ( After mixing anhydrous ethanol and each group of hydrogel sample solutions, 0.8 ml of ABTS working solution was added, and the total volume of the reaction solution was 1 ml. The measured absorbance value was A. The calculation formula is as follows:

[0084] ;

[0085] In the formula, is the absorbance of ABTS free radical working solution, is the absorbance of the hydrogel sample after free radicals are removed.

[0086] 1.7.2 Determination of DPPH free radical scavenging rate

[0087] Weigh DPPH powder, dissolve it in anhydrous ethanol and set to volume, and store it away from light. Dissolve the hydrogel in anhydrous ethanol as the sample solution. Take 2ml of DPPH solution and add 1ml of anhydrous ethanol. The measured value is ( Between 0.8-1.0). Take 2 ml of DPPH solution, add the corresponding organic solvent, and then add the sample solution. The total volume of the organic solvent and the sample is 1 ml. The value measured by mixing is the A value. The calculation formula is as follows:

[0088] ;

[0089] In the formula, is the absorbance of DPPH free radical working solution, is the absorbance of the hydrogel sample after free radicals are removed.

[0090] 1.8 Hemolysis test

[0091] The blood compatibility of OS, DS, ASB, AL and ALD hydrogels was evaluated. Fresh blood was collected from mice, and red blood cells were separated by centrifugation (1500rpm, 10min), washed three times with normal saline, and diluted to a concentration of 5% (v / v). OS, DS, ASB, AL and ALD hydrogels with a diameter of 0.2cm were mixed with a 5% (v / v) red blood cell suspension and shaken on a 37°C constant temperature shaker. After the reaction, the supernatant was centrifuged and the absorbance was measured at a wavelength of 545 nm. Red blood cells treated with 0.1% Triton-X-100 and red blood cells diluted with PBS were used as positive and negative controls, respectively. The hemolysis rate was calculated as follows:

[0092] ;

[0093] in , and These are the absorbance values ​​of the sample, PBS, and 0.1% Triton X-100, respectively.

[0094] 1.9 Antibacterial properties

[0095] The antibacterial properties of each sample were evaluated by colony counting assay. Specifically, 0.2 ml of sterile hydrogel was placed in a 24-well plate. The bacterial suspension was inoculated on the surface of each hydrogel sample, and the sample without hydrogel was used as the control group and incubated at 37°C. Then 1 ml of culture medium was added, and 20 µL of bacterial suspension was added to the solid agar plate, and photos were taken after incubation for 12 hours. The antibacterial effect of the hydrogel was calculated by counting the number of surviving colonies, and the calculation formula is as follows:

[0096] ;

[0097] Wherein, A is the number of colonies grown on the agar plate of the control group, and B is the number of colonies grown on the agar plate after co-culture with the hydrogel.

[0098] 1.10 Cytotoxicity

[0099] The cytotoxicity of the hydrogels was evaluated by the MTT assay. HaCaT cells were used to test the cytotoxicity of OS, DS, ASB, AL, and ALD hydrogels. HaCaT cells were cultured in DMEM medium and incubated in an incubator at 37°C and 5% CO2. OS, DS, ASB, AL, and ALD hydrogels were sterilized by ultraviolet light and then immersed in DMEM medium for 24 h to prepare hydrogel extracts. 1×10 4 Cells were seeded in 96-well plates. When the cell density reached 80%, the culture medium was discarded and replaced with hydrogel extract. After incubation for 24 hours, MTT solution was added to the 96-well plate and reacted for 4 hours. Subsequently, the MTT solution was removed and DMSO was added to terminate the reaction. The absorbance was measured at 490 nm to calculate the cell viability. The calculation formula is as follows:

[0100] ;

[0101] In the formula, is the absorbance of the sample, is the absorbance of the blank group, is the absorbance of the control group.

[0102] 1.11 Cell scratching

[0103] An in vitro wound healing model was constructed using HaCaT cells. The specific steps are as follows: HaCaT cells were inoculated in a 6-well plate in DMEM medium and incubated at 37°C until cell fusion reached 100%. Subsequently, the monolayer of cells was scraped off with a sterile pipette tip to form a cell-free area, and then washed with PBS to remove cell debris. After that, each group of hydrogel extracts was added to serum-free medium and incubated in the wells. Cell migration was observed at 0 hours, 24 hours, and 48 hours using an inverted microscope, and the wound area was measured using Image J software. The relative migration area of ​​cells was calculated according to the following formula:

[0104] ;

[0105] In the formula, is the initial gap area, is the gap area at time t.

[0106] 1.12 Live and dead cell staining

[0107] L929 cells (1×10 4Cells were seeded in 96-well culture plates with 100 cells / ml and incubated for 24 hours, and then cultured with different hydrogel extracts. After 1, 2, and 3 days of culture, cells were stained with calcein-AM (2 μmol / L) and PI (4.5 μmol / L) for 15 minutes in the dark at 37 °C. Cell morphology was observed and images were acquired using an inverted fluorescence microscope.

[0108] 1.13 Immunofluorescence staining

[0109] RAW 264.7 macrophages pretreated with LPS for 2 hours were seeded on round coverslips in 24-well culture plates at a density of 5000 cells / well. After 48 hours of culture with hydrogel extracts, coverslips were stained with primary antibodies against NF-κB and Nrf2 and fluorescently labeled secondary antibodies, and cell nuclei were stained with DAPI. Cell immunofluorescence images were taken using a localized fluorescence microscope.

[0110] 1.14 Hemostasis test

[0111] The validated mouse liver surface injury model and tail amputation model were used to evaluate the in vivo hemostatic effect of ALD. ICR mice were randomly divided into several groups. ICR mice were anesthetized with 4% chloral hydrate (1 mL / kg, once a day), and then the liver in the abdominal cavity was dissected and exposed. An active bleeding wound of approximately 0.4 cm × 0.4 cm was made on the liver surface with a scalpel, and after the bleeding was evaluated, equal amounts of hemostatic sponges, OS, DS, ASB, AL, and ALD were immediately applied to the wound for hemostasis experiments. The blank control group was only inflicted with active bleeding trauma without any hemostatic treatment. The total bleeding time and amount of bleeding were recorded. The tail of all ICR mice was cut off 5 cm from the end and the tail was placed vertically. The bleeding drip rate was observed to ensure that the bleeding rate after cutting was constant, and subsequent hemostasis experiments were performed. After the bleeding evaluation was completed, hemostatic sponges, OS, DS, ASB, AL, and ALD were immediately applied to the bleeding tail to ensure that the wound surface was in contact with the lightly compressed material. The tail was intermittently raised to observe the bleeding of the wound surface, and the time and amount of bleeding to completely stop were recorded.

[0112] 1.15 In vivo experiments

[0113] 1.15.1 Establishment of diabetic wound model and drug administration

[0114] Sixty male ICR mice aged 8 weeks and weighing 24-28 g were purchased from Yisi Laboratory Animal Co., Ltd., Changchun, China (animal license number: 2023-12-10-004). After the mice were adapted to laboratory conditions (temperature 22±2°C, humidity 60±5%, light-dark alternation) for one week, the type 2 diabetes (T2D) model was induced in the mice. The specific steps were as follows: After 1 week of adaptive feeding (temperature 20-25°C, humidity 40-70%, light-dark alternation for 12 hours), the mice were given a high-sugar and high-fat diet. After 4 weeks of high-sugar and high-fat diet feeding, they were fasted for 12 hours and then intraperitoneally injected with streptozotocin (STZ) three times (80, 70, and 60 mg / kg). After the injection, the mice were fed for another week, and the fasting blood glucose values ​​were measured. Mice with blood glucose values ​​higher than 11.1 mmol / L and showing polydipsia, polyuria, and weight loss were judged as T2D models. Full-thickness skin wounds were made in the dorsal area of ​​the mice. Briefly, mice were anesthetized by injecting 5% chloral hydrate (0.1 ml / 10 g). The hair on the back of the mice was removed using an electric scalpel and depilatory cream. After wiping the skin with a cotton ball of 0.9% saline, a circular full-thickness skin wound with a diameter of 1 cm was created on the back of the mice using scissors. T2D mice were randomly divided into six groups: T2D group, OS hydrogel group, DS hydrogel group, ASB hydrogel group, AL hydrogel group, and ALD hydrogel group. The wound surface of the T2D group was treated with PBS, and the wound surfaces of the other groups were treated with the corresponding hydrogels, which were changed every day. The wound area on days 0, 3, 7, 14, and 21 was recorded and measured, and the healing rate was calculated.

[0115] ;

[0116] In the formula, is the initial wound area, It is the wound area at different time points after treatment.

[0117] 1.15.2 Histopathological examination

[0118] At the end of the wound healing experiment, the mice were euthanized, and the skin tissues from the wound area were obtained and fixed with 4% paraformaldehyde. The fixed tissue samples were embedded in paraffin and cut into 6 µm sections. The degree of wound re-epithelialization and collagen deposition was evaluated by hematoxylin-eosin (H&E) staining and Masson staining techniques.

[0119] 1.15.3 Western Blot

[0120] First, the skin tissue was lysed in lysis buffer, and the supernatant was collected after high-speed centrifugation. The protein concentration was determined using a BCA kit. The samples were loaded on a 10% or 12% SDS-PAGE gel for electrophoretic separation. Subsequently, the proteins in the gel were transferred to a polyvinylidene fluoride (PVDF) membrane by electrotransfer technology and blocked in TBST buffer containing 5% skim milk powder. The primary antibodies added included MyD88, TLR4, IκBα, NF-κB, IL-1β, TNF-α, iNOS, HIF-1α, PDGFA, VEGFA, p-IκBα, and p-NF-κB, and incubated overnight at 4°C. After incubation, each PVDF membrane was washed three times with TBST at room temperature for 10 minutes each time, and then the secondary antibody was added for incubation. The membrane was washed three times with TBST. Protein bands were detected with enhanced chemiluminescence (ECL) reagents. The gray value of protein bands was analyzed using ImageJ software.

[0121] 1.16 Statistical analysis

[0122] Microsoft Excel 2020 was used for data collection. Origin 2018 was used for material property analysis. SPSS software was used for statistical analysis. Image J was used for image analysis. Adobe Photoshop 2022 was used for image combination. All data are presented as mean ± standard deviation (SD). Statistical significance was determined by t-test and one-way ANOVA. p <0.05 was considered statistically significant.

[0123] 2. Results and Discussion

[0124] 2.1 Characterization of hydrogels

[0125] 2.1.1 Characterization of AL

[0126] Figure 1 Figure AB shows the particle size and zeta potential measurement results of AL. The average particle size of AL is 107.92±0.18nm, the zeta potential is -40.04±6.46mV, and the polydispersity index (PDI) is 0.193±0.008. Figure 1The CD in the figure shows that transmission electron microscopy (TEM) shows that AL is uniformly dispersed spherical nanoparticles without obvious aggregation. The encapsulation efficiency of AL measured by high performance liquid chromatography (HPLC) is 91.69±1.84%. The zeta potential indicates the stability of the nanoformulation, and the nanoformulation with an absolute value between 30-60mV is considered to have excellent stability. The present invention obtains a more stable zeta potential and a higher encapsulation efficiency (EE); in addition, the particle size affects the blood circulation time and tissue specificity of the liposome. A smaller particle size helps the liposome circulate longer in the blood and better perform targeted delivery. The average particle size of AL obtained by the present invention is 107.92±0.18nm, which can better perform targeted delivery.

[0127] 2.1.2 Characterization of OSA

[0128] SA is a polymer composed of D-mannose and L-gulose linked alternately, with excellent biocompatibility and thickening properties. After oxidation treatment, it forms OSA, which gives it new functions and application potential. The results are as follows Figure 1 As shown in EF, in SA and OSA 1 In the H NMR spectrum, the peak at chemical shift δ=4.70 corresponds to the proton absorption peak of the solvent heavy water. The overlapping interval of δ=3.53 is the proton absorption peak of H5. Compared with SA, OSA has a proton absorption peak of H7 at δ=5.42. The peaks at δ=5.37 and δ=5.64 represent the proton absorption peaks of hemiacetal formed by the combination of aldehyde group and hydroxyl group. The changes in these characteristics indicate that OSA was successfully prepared. 1 The total number of hydrogen atoms obtained in the H NMR data shows that the degree of substitution of OSA is about 18.14%, which means that in the structure of SA, the degree of substitution of hydrogen atoms by oxidized groups is relatively high. In the FTIR spectrum, OSA has a new absorption peak at 1735 cm⁻¹, which is the characteristic absorption peak of the aldehyde group. The appearance of this absorption peak further proves that SA has successfully undergone an oxidation reaction under the action of sodium periodate to form OSA. 1 H NMR and FTIR analysis can clarify the structural characteristics and changes of OSA. These results not only verify the successful synthesis of OSA, but also provide theoretical basis and experimental support for its application in drug delivery, biomaterials and other fields.

[0129] 2.1.3 FTIR spectroscopy

[0130] By observing the absorption peaks of the infrared spectrum, the functional groups in the material can be identified. As the intensity and position of the absorption peaks change before and after the reaction, it can be determined whether a chemical reaction has occurred. Figure 1 It can be seen from the G in that as the OS hydrogel is generated, the 1735 cm -1The absorption peak of the aldehyde group disappeared, and the absorption peak shifted to 1638cm -1 The ASB infrared spectrum results show that at 1641 cm -1 The strong absorption peak at 800~1500cm is the stretching vibration of C=O. -1 Many characteristic peaks were found at 1728, 1631, and 1070 cm-1, which are the result of bending and stretching of aromatic compounds and phenolic bending of -OH. -1 The characteristic absorption peaks of AL were observed in FTIR, which were attributed to the vibration of -C=O, bending of -OH and stretching of -CN-. Compared with the ASB spectrum, the stretching vibration peak of NH at 2940 cm -1 Redshift 2935cm -1 At 1505 and 1454 cm -1 The absorption peaks at 1573 cm and 1399 cm are the bending vibration absorption peaks of NH and the stretching vibration absorption peaks of CN on the diclofenac sodium molecule. -1 COO in diclofenac sodium - The absorption peaks of (C=O) are 1285 and 748 cm -1 The absorption peaks of -CN and C-Cl are respectively. ALD is the infrared spectrum of the composite hydrogel embedded with DS and AL. -1 The absorption peak of the secondary hydrogen of diphenylamine will appear. Compared with the AL spectrum, the NH stretching vibration peak of ALD is red-shifted from 3154 to 2927 cm -1 , the peak shape becomes broader. After AL is added to ALD, the original complex characteristic peaks in the ASB "fingerprint" region are covered due to the superposition of characteristic bands, indicating that DS and AL are successfully blended in the polysaccharide hydrogel system.

[0131] 2.1.4 Morphology of hydrogel (SEM)

[0132] Figure 1H in the figure shows the images of OS, DS, ASB, AL and ALD after gelation. The morphology of the hydrogels was observed by SEM. As shown in the figure, all hydrogels showed interconnected cavities and uniform porous structures. In addition, the OS hydrogel has smooth walls due to the absence of drugs, showing an irregular porous network structure that is interconnected. DS, ASB and ALD hydrogels have thicker pore walls and larger pore sizes. The microscopic morphology of the hydrogels is similar under the scanning electron microscope, and they all show a loose porous network structure with interconnected pores. It has been reported that this porous structure helps to enhance gas exchange and nutrient transfer between the wound area and the external environment, accelerating wound healing.

[0133] 2.1.5 Rheological properties of hydrogels

[0134] like Figure 2 As shown in A and B in the figure, the storage modulus (G′) represents the elastic properties of the hydrogel, while the loss modulus (G′′) reflects its viscous properties. Rheological analysis under different frequencies and strains showed that the drug-loaded hydrogel and the blank hydrogel showed similar gel properties, and the G′ value of each group was significantly greater than the G′′ value, indicating that the elastic properties in the system dominated, which is a typical feature of elastomers. Under 1% strain conditions, the G′ value of the hydrogel was greater than the G′′ value, indicating that it was in a solid gel state. With the increase of angular frequency, the G′ value of each group of composite hydrogels remained on a stable platform and did not show frequency dependence, indicating that the prepared material had good stability. Under time-strain conditions, the G′ value of the hydrogel was always greater than the G′′ value, and both remained stable over time, indicating that the gel was in an elastic state under small oscillatory shear strain. After DS and AL were introduced into the hydrogel, its rheological properties remained good, which may be due to the formation of more hydrogen bonds between the polymer chains, making the internal network structure more perfect and enhancing the ability to resist deformation. The rheological properties of hydrogels not only reflect their viscoelastic behavior and mechanical properties, but also reveal changes in the hydrogel network structure.

[0135] 2.1.6 Swelling and degradation properties

[0136] The swelling properties of hydrogels are an important indicator for evaluating their ability to absorb and exchange water molecules and other substances from the microenvironment. The better the swelling properties, the better the permeability of the material, which helps the transfer and exchange of nutrients and metabolites required by cells. A reasonable swelling equilibrium state is an important criterion for measuring the quality of hydrogels. Excessive swelling may squeeze the tissues around the filling site, cause infection, and be detrimental to tissue repair. The swelling properties of each group of hydrogels in phosphate buffered saline (PBS) are shown in Figure 2. Figure 2As shown in C in Figure 2, the swelling rate gradually increased over time and stabilized after about 12 hours. The swelling rates of OS, DS, ASB, AL, and ALD hydrogels were 926.67±10.41%, 916±7.93%, 882.33±6.81%, 868.67±6.65%, and 824.21±10.84%, respectively. Due to its three-dimensional network structure, the hydrogel exhibited good swelling properties and did not change significantly in volume, which meant that it would not cause compression to the wound.

[0137] The degradation results of ALD are as follows Figure 2 As shown in D in the figure. It can be observed that the weight of the hydrogel increased within the first 2 hours, probably due to swelling. Subsequently, the weight of the hydrogel gradually decreased, indicating that ALD has good stability and can effectively protect wounds. Due to the water absorption and swelling of the hydrogel, the mass of each group of hydrogels increased rapidly on the first day, and the swelling rate was close to 2 times. After the second day, the hydrogel reached swelling equilibrium, and the swelling rate test results of each group were basically the same. The mass of the OS hydrogel decreased rapidly after the third day, because its developed pore network structure promoted the frequent exchange of internal and external water, accelerated the decomposition of the cross-linked Schiff base, and led to the rapid degradation of the pure hydrogel. The mass of the hydrogel containing DS remained basically stable in the first 5 days, and the morphology of each group of hydrogels was observed to be complete and elastic during the experiment. The hydrogel containing AL and DS began to gradually degrade after the 7th day, and the degradation rates of OS, DS, ASB, AL and ALD hydrogels were 51.6±1.40%, 51.1±1.76%, 52.8±1.14%, 68.8±1.06% and 64.3±0.42%, respectively. The added AL not only filled the pores of the hydrogel, but also covered the polysaccharide polymer, reducing hydration, thereby slowing down the corrosion of the cross-linking bonds and delaying the collapse of the system. With the passage of 36 days, the hydrogel sample was able to completely degrade, proving the feasibility of developing degradable ALD hydrogels.

[0138] 2.2 In vitro drug release

[0139] The pH value of diabetic wounds is an important indicator reflecting the dynamic changes of wounds and the healing process. Physiological processes including inflammatory response, collagen formation and angiogenesis will affect the pH value. Based on dynamic Schiff base bonds, ALD hydrogels are responsive under different pH conditions. The present invention explores the responsive behavior of hydrogels under different pH conditions and designs a dual release system to deliver DS and AL through multifunctional hydrogels. DS is embedded in the hydrogel skeleton, and ASB is encapsulated in liposomes. Figure 2As shown in the EF, under alkaline conditions (pH 7.4), 71.62 ± 1.02% of DS was released after 72 h, while under acidic conditions (pH 5.5), the release rate of DS was 85.03 ± 0.49%. The release rate of AL at pH 5.5 was faster than that at pH 7.4, reaching 39.19 ± 0.74% and 27.64 ± 0.52% after 24 h, respectively. Although AL continued to be slowly released over 7 days, the release of AL within 24 h was significantly lower than that of DS, indicating that the continuous collapse of the hydrogel and liposomes led to the dual release of DS and AL. This indicates that ALD hydrogel exhibits more effective release behavior in an acidic environment and is beneficial to the healing of chronic infected diabetic wounds. ALD hydrogel can not only quickly release DS with anti-inflammatory effects, but also continuously release AL with antibacterial, antioxidant and angiogenic effects. In summary, ALD hydrogel is a good drug delivery system that is beneficial to diabetic wound healing.

[0140] 2.3 Antioxidant properties

[0141] Excessive production of reactive oxygen species (ROS) in the wound area induces oxidative stress, which leads to cytotoxicity through DNA damage and enzyme reaction mechanisms. Wound dressings with antioxidant properties can accelerate wound healing by scavenging ROS. The antioxidant properties of ALD hydrogels were evaluated by ABTS and DPPH free radical scavenging experiments. Figure 3 As shown in Figure AB, all hydrogels exhibited significant ABTS and DPPH radical scavenging efficiencies, with ABTS radicals scavenging 68.84±1.05% (OS), 87.78±1.15% (DS), 91.61±0.65% (ASB), 93.45±0.49% (AL), and 94.09±0.87% (ALD), and DPPH radicals scavenging 58.87±1.03% (OS), 77.11±1.09% (DS), 88.32±1.06% (ASB), 90.12±0.81% (AL), and 92.27±1.42% (ALD), respectively. These results indicate that ALD-based hydrogels have antioxidant properties, which may be attributed to the excellent antioxidant activity of OS and AL. In addition, carboxymethyl chitosan and oxidized sodium alginate were used as polysaccharide components during the preparation of the hydrogels, which enhanced the antioxidant capacity of the hydrogels. At the same time, due to the strong antioxidant properties of ASB, the hydrogels with AL added showed superior antioxidant properties. These results indicate that ALD hydrogels are a potential biomaterial for promoting wound healing.

[0142] 2.4 Hemolytic performance

[0143] Hemolytic property usually refers to the ability of a substance or drug to cause red blood cell rupture (hemolysis), which is of great significance in the application and research of medicine and biology. When developing new drugs, evaluating their hemolytic properties on red blood cells is an important step to ensure their safety. The present invention evaluates the degree of hemolysis by measuring the absorbance of hemoglobin released after red blood cell lysis at a specific wavelength. The results of the hemolysis experiment conducted on the hydrogel in this experiment are shown in Figure 2. Figure 3 as shown in the CD. Figure 3 The C test graph in the figure shows that the color of each hydrogel group is light yellow, and the hemolysis rate is less than (≤3%). However, the positive control group (0.1% Triton X-100) is bright red and has a high hemolysis rate. The hemolysis rates of the OS, DS, ASB, AL and ALD hydrogel groups are all within the safe range and significantly lower than those of the NC treatment group (p<0.01). The specific hemolysis rates are 1.56±0.13%, 1.38±0.11%, 1.17±0.12%, 1.13±0.09% and 0.86±0.12%, respectively. The hemolysis rate of the 0.1% Triton-X-100 treatment group (99.61±1.13%) is significantly higher than that of the NC treatment group (p<0.01). The hemolysis rates of the hydrogel treatment groups are all less than 5%, so the hydrogel prepared by the present invention has good blood compatibility and can be used for subsequent treatment.

[0144] 2.5 Antibacterial properties

[0145] The ideal hydrogel dressing should not only act as a barrier between the wound and the external pathogenic environment, but also have antimicrobial properties. The present invention uses the colony counting method to evaluate the surface antibacterial activity of the hydrogel, and Escherichia coli ( E.Coli ) and Staphylococcus aureus ( S. aureus ) as representative strains of Gram-negative and Gram-positive bacteria, are usually used to detect the antibacterial properties of tissue bioengineering scaffolds. Figure 3As shown in EG, OS, DS, ASB, AL and ALD hydrogel groups all showed certain antibacterial activity against Escherichia coli and Staphylococcus aureus. The inhibition rates of OS hydrogel against Escherichia coli and Staphylococcus aureus were 54.12±1.06% and 64.41.05±1.11%, respectively. This is because the hydrogel in the OS group has the function of antibacterial and reduces wound contamination. Studies have shown that the antibacterial property of carboxymethyl chitosan mainly depends on the amino and carboxymethyl groups in its chemical structure, which interfere with and inhibit the growth and reproduction of bacteria through various mechanisms. The antibacterial mechanism of oxidized sodium alginate mainly depends on the active oxygen species and reactive groups formed during its oxidation process, which inhibit the growth and reproduction of bacteria by destroying bacterial cell membranes, chelating metal ions and inducing cell apoptosis. Compared with the control group, the inhibition rates of DS, ASB, AL and ALD hydrogel groups against Escherichia coli and Staphylococcus aureus were significantly increased (p<0.01). For Escherichia coli, the inhibition rates of DS, ASB, AL and ALD hydrogel groups were 75.04±1.43%, 81.42±1.08%, 86.45±0.86% and 90.45±1.2%, respectively. For Staphylococcus aureus, the inhibition rates of DS, ASB, AL and ALD hydrogel groups were 75.38±1.37%, 85.08±0.59%, 88.98±0.74% and 96.89±0.55%, respectively. The results showed that ALD hydrogel had an inhibition effect of more than 90% on both Escherichia coli and Staphylococcus aureus. ALD hydrogel had good antibacterial properties. In addition to its own polysaccharide matrix, it was mainly due to the rapid release of DS and the sustained release of AL, which made it have a strong antibacterial and anti-inflammatory effect. Therefore, this property can provide an antibacterial and anti-inflammatory environment for diabetic wound repair and significantly benefit the actual protection of the wound site.

[0146] 2.6 Biocompatibility

[0147] The repair of skin trauma includes four interacting and overlapping processes: hemostasis, inflammatory response, proliferation, and tissue remodeling. The epidermis is mainly composed of keratinocytes, which provide a physical barrier to protect the body from external factors and pathogens. Cell migration is essential for wound healing. The present invention uses the human immortalized keratinocyte cell line HaCaT to perform the MTT test to evaluate the effect of hydrogels on cell viability. The results showed that DS and AL hydrogels had no significant differences compared with the blank control group, were non-toxic, and had no significant effect on cell biocompatibility. The scratch test showed that ALD hydrogel significantly promoted the wound repair of HaCaT cells within 0-48 hours (p<0.01). Figure 4As shown in BC, the cell scratch repair rates of the NC treatment group at 24 hours and 48 hours were 52.02 ± 1.50% and 71.46 ± 1.14%, respectively. The repair rates of the OS, DS, ASB, AL and ALD treatment groups at 24 hours were 57.92 ± 1.46%, 67.71 ± 0.43%, 63.35 ± 0.51%, 73.14 ± 0.27% and 79.90 ± 0.31%, respectively; and the repair rates at 48 hours were 76.11 ± 047%, 79.15 ± 0.68%, 78.49 ± 0.52%, 79.15 ± 0.68% and 94.34 ± 0.71%, respectively. These results indicate that ALD hydrogel significantly improves the migration and proliferation ability of HaCaT cells and maintains the normal function of keratinocytes.

[0148] Fibroblasts are key in wound healing. L929 cells are a mouse fibroblast cell line. The survival status of L929 cells was evaluated by cell live-death staining assay. Figure 5 The results in Figure A show that the L929 cells showed normal morphology, and few dead cells were found in each group, which was consistent with the MTT assay. After 3 days of culture, an increase in the density of the cell population was clearly observed, indicating that L929 cells were able to proliferate in the hydrogel, which may be attributed to the excellent biocompatibility and dual dynamic network structure of the ALD hydrogel.

[0149] Macrophages are key inflammatory and immune cells that play an important role in the inflammatory process by secreting a large number of pro-inflammatory mediators (such as COX-2, iNOS and pro-inflammatory cytokines such as TNF-α and IL-1β). Lipopolysaccharide (LPS) is a commonly used inflammatory stimulant used to activate macrophages or monocytes. Studies have found that LPS stimulation can induce macrophages to produce a large number of inflammatory mediators and pro-inflammatory cytokines. LPS-activated RAW264.7 macrophages are a common in vitro model for studying the inflammatory stage of wound healing, so the present invention chooses it to evaluate the anti-inflammatory ability of hydrogels. In the present invention, macrophages were pre-activated with LPS and then incubated with various hydrogel extracts for 48 hours. The results showed (see Figure 5 In Figure B, MTT assay showed that compared with the untreated group, after 4 µg / ml LPS induction, cell viability decreased to 65.86 ± 0.81%, indicating that LPS stimulation caused an inflammatory response, leading to a decrease in cell viability. After treatment with ALD hydrogel extract, the cell survival rate increased to 112.32 ± 0.97%, significantly increasing the cell proliferation rate (p < 0.05), mainly because the hydrogel inhibited the inflammatory response of macrophages.

[0150] During the inflammatory stage of diabetic wounds, excessive ROS leads to persistent oxidative stress, which in turn causes a decrease in Nrf2 expression. Nrf2 is a key factor in the cellular antioxidant protection system that protects cells from environmental damage. NF-κB is an important inflammatory signal regulator that coordinates the expression of multiple pro-inflammatory genes. The slow healing of wounds in diabetic patients is closely related to factors such as increased oxidative stress, persistent inflammatory response, and microvascular complications. In order to determine the effect of ALD hydrogel on LPS-induced oxidative stress and pro-inflammatory factor expression in macrophages, the present invention was conducted by Figure 5 C immunofluorescence was used to study the levels of Nrf2 and NF-κB. The results showed that the expression of Nrf2 in the LPS-treated group decreased significantly, while ALD hydrogel promoted the nuclear translocation of Nrf2 and the increase in fluorescence level, thereby alleviating cellular oxidative stress and protecting cells from apoptosis through the expression of antioxidant enzymes. In addition, the LPS-treated group activated NF-κB in macrophages, leading to its nuclear translocation, while ALD hydrogel significantly inhibited this trend. These results suggest that ALD hydrogel can alleviate LPS-induced macrophage inflammatory damage by upregulating Nrf2 and inhibiting the NF-κB signaling pathway, thereby potentially improving wound healing in patients with diabetes.

[0151] 2.7 In vivo hemostatic properties

[0152] The hemostatic property of ALD is an important indicator for evaluating its application in tissue engineering. ALD controls bleeding through the ability of its matrix to encapsulate blood cells, platelets and other coagulation factors and its structural similarity to natural fibrin. In addition to this, ALD can also stop bleeding by physical blockage. The pore size of ALD is so tight that they can form a three-dimensional mesh structure, which helps to physically block the flow of blood. When ALD contacts the bleeding point, the hydrogel adheres to the wound surface and quickly adsorbs platelets and red blood cells in the blood. This physical adhesion and the formation of a fiber mesh can quickly slow down or stop the flow of blood. Their emergency hemostatic properties were further studied using the in vivo mouse tail amputation model and liver hemostasis model, and acute bleeding events in the trunk and visceral organs were evaluated. Figure 6As shown in the AE in the data, when liver bleeding occurred and the bleeding time exceeded 160s, the hemostasis time was prolonged and the amount of bleeding was large (160±2.51s and 202.33±7.09 mg, respectively). The hemostasis time of the OS group, DS group, ASB group, AL group, and ALD group was 127±8.19 s, 112±6.8 s, 86±5.29 s, 82.6±6.43, and 79±5.13, respectively, and the amount of bleeding in the OS group, DS group, ASB group, AL group, and ALD group was 92±6.42 mg, 74±5.03 mg, 58±6.93 mg, 49±4.04 mg, and 37.67±7.51 mg, respectively. In the in vivo mouse tail dissection model, the improvement of hemostasis efficiency was similar to that in the mouse liver hemostasis model. The hemostasis time of the control group was 159±1.15 s, and the amount of bleeding was 161±1.73 mg. The hemostatic time of OS group, DS group, ASB group, AL group and ALD group was 99±9.02 s, 93±1.53 s, 87±2.65 s, 78±3.05 s and 67.6±2.52 s, respectively, and the hemostatic volume of OS group, DS group, ASB group, AL group and ALD group was 107±2.31 mg, 84±2.08 mg, 73±4.16 mg, 61±6.56 mg and 55±4.35 mg, respectively. The present invention also established a commercial hemostatic sponge control group to examine the hydrogel material with superior hemostatic properties as a wound dressing, and the results showed that the hemostatic effect of the material group was better than that of the commercial sponge group in the tail of liver bleeding model. The above results suggest that materials with functional components can effectively improve bleeding control. It is proved that ALD hydrogel has good in vivo hemostatic properties, which is also of great significance for the application of wound dressings.

[0153] 2.8 In vivo experiments

[0154] 2.8.1 Wound healing in diabetic mice

[0155] Under the condition of hyperglycemia, excessive ROS and inflammatory factors will damage angiogenesis, inhibit normal wound healing, and lead to chronic wound non-healing. In order to explore its effect on skin wounds and the prospects for clinical drug development, the present invention established an in vitro diabetic patient wound model to evaluate the therapeutic efficacy of ALD hydrogel. Figure 7 In A of the present invention, a T2D diabetic mouse model was used to monitor the changes in mouse weight and blood sugar. After successful modeling, full-thickness skin wounds were generated on the back of the mouse, and local treatment was performed with different hydrogels (OS, DS, ASB, AL, ALD). The untreated wounds were used as the control group (T2D group). Figure 7As shown in B, wound healing was observed on days 0, 3, 7, 14, and 21. After 3 days of treatment in each hydrogel group, the epidermis of the diabetic skin wound tissue cultured in vitro gradually thickened and migrated to the center of the wound, among which ALD had the most significant effect. After one week of treatment, the wound healing in the T2D group was not obvious, there was exudate, and the wound contraction rate was 62.64±3.31%. In contrast, DS and AL significantly promoted wound healing (p<0.05), with healing rates of 74.06±1.19% and 76.36±1.08%, respectively. The healing rate of ALD hydrogel was 81.66±1.91%, and ALD had the fastest healing speed. Quantitative analysis confirmed this result ( Figure 7 C in the figure). On the 21st day, the wounds treated with ALD hydrogel were basically healed, while the wound areas of T2D and OS groups were 82.34±1.06% and 91.13±0.81%, respectively. In addition, the healing speed of DS and AL hydrogel groups was faster than that of T2D group, but slower than that of ALD group. This indicates that ALD can promote epidermal cell proliferation and thus promote epidermal regeneration. Persistent high inflammatory response is one of the key factors that hinder wound healing in diabetic patients. The combination of rapid release of DS and slow release of AL in OS hydrogel can inhibit excessive inflammatory response activity of wounds and effectively promote the healing of infected diabetic wounds, which is better than using them alone.

[0156] 2.8.2 Histopathological analysis

[0157] Granulation tissue formation, re-epithelialization, collagen deposition and angiogenesis are typical signs of wound healing. AL has antioxidant, anti-inflammatory and angiogenic properties. In order to explore the effects of ALD hydrogel, the present invention conducted histopathological analysis on mouse wounds. H&E staining results showed ( Figure 7 D in the figure), the granulation tissue in the blank hydrogel group (OS), DS treatment group and AL group gradually decreased, indicating that wound repair has shifted from the inflammatory phase to the remodeling phase. In contrast, after 21 days of treatment, the T2D group still had no epidermis formation, accompanied by a large number of inflammatory cell infiltrations, indicating that its wound was still in the inflammatory phase, and the continued inflammatory phase was not conducive to wound healing. At the same time, the present invention observed that the new epidermis in the OS, DS, ASB, AL and ALD hydrogel groups was almost complete, and the number of inflammatory cells decreased. The epidermal tissue in the ALD group was tighter, and there was no obvious peeling of the epidermal tissue compared with the OS, DS and ASB groups. This is mainly attributed to the inherent function of the OS hydrogel, the effective release of DS reduced the inflammatory response, and the release of AL accelerated angiogenesis. Masson staining was used to evaluate the collagen deposition in the wound healing area. The results of Masson staining showed that the collagen content of each group increased, and the collagen deposition of the DS, AL and ALD groups was more significant compared with the T2D group. In particular, the collagen fibers in the ALD group were denser and more orderly than those in the AL group, and the epidermal thickness and hair follicles increased significantly. The quantitative analysis results are shown in Figure 2. Figure 7In summary, ALD can regulate inflammatory response, promote epithelial regeneration, angiogenesis and collagen deposition, thereby accelerating diabetic wound healing.

[0158] 2.8.3 ALD hydrogel promotes wound healing via TLR4 / NF-κB / MyD88 and HIF-ɑ signaling pathways

[0159] Poor wound healing in diabetes is one of the common and difficult problems in clinical practice. Its main obstacle is persistent chronic inflammation. In order to evaluate the anti-inflammatory effect of ALD hydrogel and explore the role of TLR4 / NF-κB / MyD88 signaling pathway in diabetic wound healing, the present invention studied the effect of inhibition of this pathway on wound healing. TLR4 is a key receptor in the innate immune system, which mainly activates the downstream NF-κB signaling pathway through the MyD88-dependent pathway. In the diabetic environment, hyperglycemia and oxidative stress often lead to overexpression of TLR4, thereby activating the NF-κB signaling pathway and triggering a series of inflammatory responses. The protein expression levels of the TLR4 / MyD88 / NF-κB signaling pathway and inflammatory factors TNF-α, IL-1β, and iNOS were detected by Western Blot method. Figure 8 The AH in the figure showed that the levels of TLR4, MyD88, p-IκBα, p-NF-κB, TNF-α, IL-1β and iNOS in the diabetic model T2D group were significantly increased (p < 0.05), which was consistent with the results of H&E staining. The wound surface was severely infiltrated with an increase in inflammatory cells. After DS and AL intervention, the expression of inflammatory factors in the wound tissue was significantly lower than that in the OS group, and the number of inflammatory cells decreased. However, the expression of inflammatory factors in the ALD hydrogel group decreased most significantly (p < 0.01), indicating that ALD hydrogel can promote wound healing by inhibiting the TLR4 / MyD88 / NF-κB signaling pathway. Angiogenesis is crucial for the healing of diabetic wounds. In this process, the HIF-α (hypoxia-inducible factor-α) signaling pathway plays a key role. Diabetic wounds are usually accompanied by local hypoxia, and the activation of HIF-α is a natural response to this hypoxic state. The present invention uses Western Blot technology to detect the expression levels of HIF-α, VEGFA and PDGFA proteins. As Fig. 9As shown in Figures AD, the protein expression levels of HIF-α, VEGFA, and PDGFA were decreased in the T2D group, while the expression of related growth factors was upregulated in the DS, AL, and ALD groups. This suggests that ALD upregulates the expression of vascular endothelial growth factors (such as VEGFA and PDGFA) through HIF-α, thereby promoting angiogenesis and improving the blood and oxygen supply to the wound area. New blood vessels can provide necessary nutrients and oxygen to promote tissue repair, making good blood supply the key to wound healing. However, overactivation of the TLR4 / NF-κB / MyD88 signaling pathway inhibits angiogenesis. The results show that by inhibiting this pathway, not only can the wound's anti-infection ability be enhanced, but the expression of angiogenesis-related genes (such as VEGF) can also be upregulated to promote the formation of new blood vessels. This improves the blood flow and nutrient supply to the wound area, providing a good environment for cell migration and tissue reconstruction.

[0160] The present invention has developed a new type of ALD hydrogel based on dynamic Schiff base bonds, which has multiple functions, including hemostasis, anti-oxidation, anti-inflammatory, and spatiotemporal delivery properties. It is used as a wound dressing to stop bleeding while reducing bacterial infection, relieve oxidative stress, inhibit inflammatory response, promote collagen deposition and angiogenesis, and accelerate the healing of chronic diabetic wounds; in addition, the dynamic Schiff base bond also gives it excellent mechanical strength, biocompatibility and pH responsiveness; by encapsulating DS and AL into different spatial positions of OS hydrogel, a spatiotemporal controlled delivery system is constructed. In vitro and in vivo experiments show that ALD hydrogel has rapid hemostasis, good biocompatibility and intrinsic antibacterial and antioxidant capabilities. The rapid release of DS shows significant antibacterial and anti-inflammatory effects, while the sustained release of AL can promote angiogenesis, thereby comprehensively accelerating wound healing and providing a more effective wound healing treatment plan for diabetic patients.

[0161] The above specific examples are used to illustrate the present invention, which is only used to help understand the present invention and is not intended to limit the present invention. For those skilled in the art of the present invention, according to the idea of ​​the present invention, some simple deductions, deformations or substitutions can be made. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A method for preparing a pH-responsive dual-release hydrogel for promoting diabetic wound healing, characterized in that: The following steps are involved: Step 1: Preparation of oxidized sodium alginate; Using sodium periodate to oxidize sodium alginate to prepare oxidized sodium alginate; Step 2: Preparation of astilbin liposomes; First, a solution consisting of astilbin, soybean lecithin and cholesterol in a ratio of 10:1:1 was dissolved in a mixed solvent of 5 ml methanol and 20 ml chloroform; then, the organic solvent was removed by rotary evaporation in a 35°C water bath to form a dry lipid film, which was then treated in a freeze dryer to completely remove the residual solvent; then, 10 ml of 0.02 mol / L phosphate buffer was added to the lipid film and rotated to form a liposome suspension; finally, the liposome suspension was ultrasonically treated using an ultrasonic processor in an ice water bath, and then the unencapsulated astilbin was removed by centrifugation; Step 3: Synthesis of ALD hydrogel; Oxidized sodium alginate solution was prepared with distilled water, and astilbin liposomes were added to obtain OSA@AL solution; carboxymethylated chitosan and diclofenac sodium were dissolved in distilled water to prepare CMCS@DS solution; OSA@AL solution and CMCS@DS solution were mixed in equal volumes, and ALD hydrogel, i.e., pH-responsive dual-release hydrogel, was prepared through Schiff base reaction.

2. The method for preparing a pH-responsive dual-release hydrogel for promoting diabetic wound healing according to claim 1, characterized in that: The specific steps of step 1 are: taking 1.0 g of sodium alginate powder and dissolving it in 50 ml of distilled water, then adding 1.08 g of sodium periodate to the sodium alginate solution, and reacting it for 5 hours under light-proof conditions; then adding 1.5 ml of ethylene glycol, and continuing the reaction for 1 hour to neutralize the unreacted sodium periodate; using a dialysis bag with a molecular weight cutoff of 3500 Da for 3 days of dialysis, and obtaining white flocculent oxidized sodium alginate by freeze drying.

3. The method for preparing a pH-responsive dual-release hydrogel for promoting diabetic wound healing according to claim 1, characterized in that: The pH of the phosphate buffer in step 2 was 7.2, and the liposome suspension was sonicated for 5 minutes using an ultrasonic processor with a power of 100 W in an ice water bath.

4. The method for preparing a pH-responsive dual-release hydrogel for promoting diabetic wound healing according to claim 1, characterized in that: The specific operation of removing the unencapsulated astilbin by centrifugation in step 2 is: centrifuging at 12,000 rpm for 30 minutes at 4°C to collect the drug-loaded lipid nanoparticles, i.e., astilbin liposomes.

5. The method for preparing a pH-responsive dual-release hydrogel for promoting diabetic wound healing according to claim 1, characterized in that: In step 3, the concentration of the oxidized sodium alginate solution was 10%, astilbin liposomes containing 100 μmol of astilbin were added, the concentration of carboxymethylated chitosan was 10%, and the amount of DS added was 20 μg / ml.

6. Use of the pH-responsive dual-release hydrogel prepared by any one of the methods of claims 1 to 5 in preparing hemostatic materials.

7. Use of the pH-responsive dual-release hydrogel prepared by any one of the methods of claims 1 to 5 in preparing materials for promoting wound healing.

Citation Information

Patent Citations

  • Traditional Chinese medicine composition for treating gout

    CN108686102A

  • Drug-loaded liposome hydrogel as well as preparation and application thereof

    CN115887744A